Internationale Sozialpolitik als Netzwerkpolitik? Horizontale Vernetzung und vertikale Politikverflechtung im Aufgabenbereich. der Internationalen Arbeitsorganisation (ILO) - Zascke, Wolfgang (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1994)
The analysis of international networks with the eyes of the critical-rational theory's paradigm-rivalry overestimates the fresh start in comparison to the continuity of International Relations. The optimistic view of liberal, intermediate cross-linking has to be partially corrected in respect to the policy-area or regime analysis of the ILO's international social policy which refers to the domination aspect of issue-orientated cross-linking and the strong position of national and local intervention administration in the vertical policy amalgamation. Additionally, other acting possibilities, unexploited so far, are made visible. The comparison of ideology, politics, structure and process of international social policy leads to corresponding recommendations for the ILO-politics and for the policy-area-analysis in the dominating liberal school of International Relations